2007
DOI: 10.1523/jneurosci.3750-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Deep Brain Stimulation of the Nucleus Accumbens Region Suppresses Neuronal Activity and Selectively Modulates Afferent Drive in Rat Orbitofrontal CortexIn Vivo

Abstract: High-frequency deep-brain stimulation (DBS) of the nucleus accumbens (NAc) region is an effective therapeutic avenue for patients with treatment-resistant obsessive-compulsive disorder (OCD). Imaging studies suggest that DBS acts by suppressing the aberrant metabolism in the orbitofrontal cortex (OFC) that is a hallmark of OCD; however, little is known about the mechanisms by which this occurs. We examined the effects of 30 min NAc DBS at 130 Hz on spontaneously active OFC neurons and local field potentials (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 74 publications
11
131
0
1
Order By: Relevance
“…That is, although it is clear that DBS to this region alleviates symptoms of depression (Schlaepfer et al, 2008), the mechanism of this improvement remains unknown. For example, it is possible that DBS-driven overstimulation of nucleus accumbens target or afferent regions (McIntyre et al, 2004;McCracken and Grace, 2007) drives the efficacy of this procedure. Consistent with this 'network modulation' idea, DBS to other brain regions such as the subgenual cingulate is also effective at alleviating depression symptoms (Mayberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…That is, although it is clear that DBS to this region alleviates symptoms of depression (Schlaepfer et al, 2008), the mechanism of this improvement remains unknown. For example, it is possible that DBS-driven overstimulation of nucleus accumbens target or afferent regions (McIntyre et al, 2004;McCracken and Grace, 2007) drives the efficacy of this procedure. Consistent with this 'network modulation' idea, DBS to other brain regions such as the subgenual cingulate is also effective at alleviating depression symptoms (Mayberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars conclude that the influence of DBS on the neurological network is more complicated than simply damaged surgery and that DBS therapy may affect the neuronal somas and the two-way activation function of axons (21,22). Previous studies have reported that various neurotransmitters, including glutamic acid and dopamine, are released following DBS (23,24).…”
Section: Mechanisms Of Dbsmentioning
confidence: 99%
“…Other possible mechanisms of action for high-frequency DBS include local neuronal inhibition with concomitant activation of surrounding fibres, thus resulting in increased synaptic output [73] and activation of afferent axon terminals (e.g. the cortical inputs in the case of STN or NAcc HFS [73,74]; for a review, see [75]). The functional outcome of these complex putative mechanisms of action is uncertain and is probably variable, depending on the specific anatomophysiological arrangements of each target region.…”
Section: Mechanisms Of Action Of Dbsmentioning
confidence: 99%